An extensive chronic aortic dissection presenting with acute embolic stroke. Issue 5 (13th October 2017) - Basnet, Sijan; Mainali, Naba Raj; Tharu, Biswaraj; Dhital, Rashmi; Poudel, Dilli Ram
ABSTRACT: Herein, we present a rare case of extensive chronic aortic dissection with extension to bilateral subclavian arteries, bilateral common carotid arteries, right internal carotid artery, bilateral proximal external iliac arteries and simultaneous presentation of acute embolic stroke and seizure. The rarity of this case presentation and the presence of neurological features necessitated a high index of clinical suspicion to reach the definitive diagnosis. This study also demonstrates a unique situation requiring correlation between chronic aortic dissection and multi-organ system dysfunction from chronic ischemia.